Surface modification of steel 20 by the method of chemical-thermal treatment by annealing in a muffle furnace - Shevchuk, E.P.; Nurumkanov, D.K.; Muratbekov, B.M.; Ahmetzhanov, B.; Plotnikov, V.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article is devoted to the current problem related to the hardening of the surface layers of metal materials, including steel parts. The authors of the article describe the methods of chemical and thermal treatment of surface layers of materials to effectively improve the durability of machine parts and tools operating under various conditions of wear, at high temperature and force effects. The method of saturation of samples of iron plates by means of coating them with boron-containing mixtures in different volume proportions and their subsequent annealing in a muffle furnace is considered. The results of studies of the microhardness and thickness of the diffusion layer are given.
Муфельді пеште жану арқылы химиялық термиялық өңдеу əдісімен 20 болаттың бетін модификациялау
Модификация поверхности стали 20 методом химико-термической обработки путем отжига в муфельной печи
Keywords: steel 20; saturating mixture; boration; diffusion layer; microhardness; chemical-thermal treatment; muffle furnace